1999
DOI: 10.1037/h0080383
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environment on adolescent mental health and behavior: Structural equation modeling.

Abstract: This study uses structural equation models to describe how objective neighborhood, perceived neighborhood, and environmental support predict mental health; 792 adolescents responded to highly structured interviews. The effect of objective environment on mental health was mediated through its influence on perceived neighborhood. Environmental support mitigated negative perceptions of environment and the effect of perceived environment on mental health, while exposure to violence augmented the negative effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 48 publications
(52 reference statements)
3
52
0
Order By: Relevance
“…We removed this path from the model. Stiffman et al (1999) observed a similar result: their measure of actual neighborhood conditions did not directly impact on the mental health status of the adolescents in their study. Second, time spent on the street did not appear to impact experiences of violence in the neighborhood, and thus this path was removed from the model.…”
Section: Path Analysessupporting
confidence: 68%
See 2 more Smart Citations
“…We removed this path from the model. Stiffman et al (1999) observed a similar result: their measure of actual neighborhood conditions did not directly impact on the mental health status of the adolescents in their study. Second, time spent on the street did not appear to impact experiences of violence in the neighborhood, and thus this path was removed from the model.…”
Section: Path Analysessupporting
confidence: 68%
“…Using structural equation modeling, Stiffman et al (1999) examined the pathways between objective neighborhood conditions, perceived neighborhood conditions, environmental support, and mental health outcomes among adolescents living in inner-city areas of St. Louis. Although they found no direct impact of neighborhood conditions on mental health, they did find an indirect pathway through individual perceptions of neighborhood conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A direct link between the environment and mental health has been established in a variety of urban settings. 26,27 Participation in informal activities has been associated with beneficial health outcomes. [28][29][30][31] However, recent reports have questioned the health implications of social capital in neighborhood life.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that perceptions of environments are consistently better predictors of outcomes than objective measures, such as ratings of the physical appearance of the neighborhood, census information on crowding and SES, etc. (e.g., Stiffman et al 1999). However, the problem with basing research findings on people's perceptions is that they are subjective-unique to the experiences of the participant and of questionable authority to be generalized to others.…”
Section: Limitationsmentioning
confidence: 99%